Rethinking the Urban Fringe: A Scoping Review of Theories, Models and Applications in Contemporary China - Shuo Wu; R. B. Radin Firdaus; Zhennan Lyu; Sarjiyanto Sarjiyanto (The Directorate for Research and Innovation, Institut Teknologi Bandung, 2025)
This scoping review explores how the urban fringe is conceptualized and applied in the context of China’s rapid urbanization. Drawing on the PRISMA framework, a systematic search of the Web of Science (WoS) and CNKI databases identified thirteen relevant studies published between 2014 and 2024. The review synthesizes key theoretical approaches, spatial models, and empirical applications to examine the evolving characteristics of urban fringe zones. The findings reveal that economic transformation, changing social structures, and spatial heterogeneity jointly shape urban fringe development in China. While the urban fringe plays a critical role in mediating urban expansion, land-use change, and governance innovation, a notable gap remains: the absence of a universally applicable framework to define and manage urban fringe areas, largely due to regional variability and fragmented institutional structures. This study argues for the development of flexible yet standardized governance models that accommodate local conditions while supporting sustainable urban growth. The review contributes to the theoretical refinement of peri-urban studies and offers actionable insights for urban planners and policymakers seeking to manage the tensions between rural preservation and urban expansion in a rapidly developing region.